Ensaios destrutivos e não destrutivos para caracterização de estruturas em concreto: exemplos e interpretação de resultados - Fonseca, Pedro Augusto Ribeiro da (2024)
This paper presents some methods for evaluating reinforced concrete structures, focusing on destructive and non-destructive tests. The main objective is to provide a comprehensive understanding of the structural characterization of reinforced concrete, highlighting the importance of effective inspection techniques to ensure the durability and safety of buildings. The justification for the study emphasizes the need for accurate methodologies to identify structural problems and implement effective corrective measures. It addresses the main tests used to characterize structures with a focus on conservation and other factors that cause deterioration over the years. The theoretical basis explores the main concepts and techniques used in the evaluation of reinforced concrete structures. In the presentation and discussion of the data, the study was based on references from several authors, who performed tests on different structures, analyzing and interpreting the results according to the parameters established in the standards. This paper presents practical examples of the application of procedures and techniques, explaining how and where to use them, in addition to detailing the purpose of each test, illustrated clearly and precisely with concrete case studies.